Anatomic and histologic analysis of the mid-substance and fan-like extension fibres of the anterior cruciate ligament during knee motion, with special reference to the femoral attachment - Tomoyuki Mochizuki (2018)
Purpose: The purpose of this study is to evaluate the morphology of the mid-substance and fan-like extension fibres of ACL during knee motion with reference to the femoral attachment. Methods: This study used six fresh-frozen cadaveric knees and 22 embalmed cadaveric knees to macroscopically evaluate morphological changes in the ACL attachment during knee motion. Three embalmed specimens fixed at knee extension and another three specimens fixed at 120° flexion were used for histologic observations. Results: The fan-like extension fibres were adhered to the bone surface and the fibre location and orientation in relation to the femoral surface did not change, regardless of the knee flexion angle, while the orientation of the mid-substance fibres in relation to the femur did change during knee motion. During knee flexion, a fold in the ACL femoral attachment was observed at the border between the mid-substance and the fan-like extension fibres. The attachment of the mid-substance fibres was significantly smaller than the attachment of the fan-like extension fibres. Conclusion: The present study clarified anatomic and histologic character of the mid-substance fibres and fan-like extension fibres, and provided critical information for future clinical and biomechanical studies concerning both two different fibres. Specifically for ACL reconstruction, it is difficult to reconstruct the natural fan-like extension fibres by creating a tunnel at the femoral and tibial ends of each fibre bundle, although the mid-substance fibres can be reconstructed by such procedures. © 2013 Springer-Verlag Berlin Heidelberg.